2011
DOI: 10.1590/s1517-86922011000500010
|View full text |Cite
|
Sign up to set email alerts
|

Yo-Yo IR2 test e teste de margaria: validade, confiabilidade e obtenção da frequência cardíaca máxima em jogadores jovens de futebol

Abstract: Os objetivos do presente estudo foram: i) avaliar a validade de constructo do Yo-Yo Intermittente Recovery Test Level 2 (Yo-Yo IR2) e do teste de Margaria (TM) com o desempenho em alta intensidade de exercício durante jogos oficiais em jogadores de futebol; ii) verificar a confiabilidade (teste-reteste) dos dois testes; iii) comparar os valores da frequência cardíaca máxima (FCM) obtida nesses protocolos e em jogo. Dezoito jogadores (média ± DP; idade 14 ± 0,8 anos, estatura 172 ± 9cm, peso 64,3 ± 8,5kg) perte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
(70 reference statements)
1
1
0
Order By: Relevance
“…Regarding the main correlations between variables, it seems that the positive value between HRmax and distance in the YOYOIR1 among men results from the fact that these male athletes exhibit better physical fitness and, therefore, achieve higher HR until exhaustion in the test (Bangsbo et al, 2008). Data from the present study corroborate Silva et al (2011), who found a high correlation (r = 0.71) between Yo-Yo IR2 and HRmax in soccer players. However, as shown in the last panel ( figure 3, panel D), the women did not present a significant correlation (r = 0.01), and the distance reached by them may have been insufficient to reach HRmax, and this can be explained by the fact that most have never performed maximal aerobic efforts.…”
Section: Physical Fitness In Amateur Paddle Tennis | 49supporting
confidence: 87%
“…Regarding the main correlations between variables, it seems that the positive value between HRmax and distance in the YOYOIR1 among men results from the fact that these male athletes exhibit better physical fitness and, therefore, achieve higher HR until exhaustion in the test (Bangsbo et al, 2008). Data from the present study corroborate Silva et al (2011), who found a high correlation (r = 0.71) between Yo-Yo IR2 and HRmax in soccer players. However, as shown in the last panel ( figure 3, panel D), the women did not present a significant correlation (r = 0.01), and the distance reached by them may have been insufficient to reach HRmax, and this can be explained by the fact that most have never performed maximal aerobic efforts.…”
Section: Physical Fitness In Amateur Paddle Tennis | 49supporting
confidence: 87%
“…After testing the normality of the data through the Shapiro–Wilk and Levene tests, a paired t -test was performed for comparison between the days. To analyze the reliability, the r -test was used (Pearson’s linear correlation), classified according to da Silva et al 30 as very low (<0.20), low (0.20–0.39), moderate (0.40–0.59), high (0.60–0.79), and very high (0.80–1). In analyzing the consistency among the variables, intraclass correlation coefficient (ICC) was used, as categorized by Santos et al 31 and Sánchez and Echeverry: 32 not acceptable (<0.70), acceptable (0.70–0.79), good agreement (0.80–0.89), and excellent agreement (>0.90).…”
Section: Discussionmentioning
confidence: 99%
“…In studies on the determination of HR max in team sports, several maximal physical tests have been used, i.e., laboratory tests on the treadmill 10,15,16 ; continuous running field tests 9,11 and intermittent running field tests 8,12,15,16 , which have ecological validity, as for example, the Yo-Yo intermittent recovery level 1 test (YYIR-1), a test with high reproducibility, sensitivity, validity to access HR max , indicate to intermittent sports 15 . However, the HR max determined in soccer official matches 7,11,12 and basketball simulated match 17 has shown higher values in comparison to physical tests, while only one study with futsal players reported similarity between match and physical test HR max 18 . Although HR measured at maximal physical exertion is more trustworthy in establishing HR max , a better way to determine HR max , in the absence of equipment to determine the HR max at maximum effort, the use of agepredicted equations should be cautious, considering that there are many age-predicted HR max equations validated for distinct populations 9,16,17 , and the use of general agepredicted equations may generate an important prediction error when utilized in specific sports, jeopardizing training prescription 3,17 .…”
Section: Introductionmentioning
confidence: 93%
“…In practice, HR max can be determined in different ways, measured in maximum physical effort tests [7][8][9][10] and, specifically in team sports, measured in official match [11][12][13] , in which the player seeks his maximum performance to win against the opponent. However, although most HR monitors available on the market allow measuring and storing HR values with high reliability 14 and have become popular, in practice, not all teams have the equipment to determine HR max .…”
Section: Introductionmentioning
confidence: 99%